Permeation enhancers in transdermal drug delivery systems: a new application of cyclodextrins (Revista Brasileira de Ciências Farmacêuticas, 2002)
The present work is a short revision about transdermal permeation enhancers, their mechanism of action including some examples. Routes of permeation across the skin and transdermal delivery are also described. We focus cyclodextrins and their derivatives, structure, chemical properties, formation of inclusion complexes and their action as excipients in transdermal drug delivery systems. Cyclodextrins are a very important group of excipients used in pharmaceutical technology. One of the most extraordinary properties of cyclodextrins is their ability to increase transdermal drug delivery without affecting the barrier function of the skin.